Composite diaphragm, preparation method thereof and battery
By applying a composite coating of high-entropy alloy aerogel and solid electrolyte on the lithium battery separator, the problem of insufficient thermal stability and interface stability of the existing separator is solved, which significantly improves the high-temperature performance and cycle stability of the battery and enhances the safety of the battery.
Patent Information
- Application Number
- CN202411746020.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The thermal stability and interface stability of existing lithium battery separators are poor, resulting in poor thermal management of batteries under extreme operating conditions, affecting battery life and safety.
A composite separator is used, which consists of a base film and a coating on the surface on the thickness direction of the base film. The coating contains a high-entropy alloy aerogel and a solid electrolyte, and is prepared by the sol-gel method.
It significantly improves the high-temperature performance and cycle stability of the battery, improves the overall thermal stability and structural stability of the battery, reduces the internal resistance of charge and discharge, and enhances the safety of the battery.
Smart Images

Figure CN119833889A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a composite diaphragm and a preparation method thereof, and a battery. Background Art
[0002] With the rapid development of the new energy vehicle industry, the requirements for the safety and energy density of automotive lithium batteries are increasing. Especially under extreme conditions, the large amount of heat generated inside the battery may cause the temperature to rise rapidly, which will affect the battery life and may cause safety problems. The main function of the diaphragm in the battery is to prevent physical contact between the anode and cathode poles, and also serve as a lithium ion transport channel in the battery; and in terms of battery safety, the diaphragm plays an important role. Therefore, the development of a diaphragm with excellent thermal stability has become the key to improving the thermal management of lithium batteries.
[0003] In the related art, some diaphragms include a base film and a coating disposed on the base film, and the coating can increase the puncture strength and high temperature resistance of the diaphragm. However, the existing diaphragm coating still has problems such as poor thermal stability and unstable interface. Therefore, it is urgent to provide a composite diaphragm to solve the problems existing in the prior art. Summary of the invention
[0004] In view of this, the present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present invention provides a composite diaphragm and a preparation method thereof and a battery, which can alleviate the problems of poor thermal performance and unstable interface of the existing diaphragm, improve the high temperature performance and cycle stability of the battery, and also have low preparation cost, simple process, and can realize the technical requirements of industrialization.
[0005] In order to solve the above technical problems, this application is implemented as follows:
[0006] According to one aspect of the present application, an embodiment of the present application provides a composite diaphragm, the composite diaphragm comprising a base film, and a coating disposed on at least one side surface of the base film along a thickness direction;
[0007] The coating comprises a composite material comprising a high entropy alloy aerogel and a solid electrolyte.
[0008] In addition, the composite diaphragm according to the present application may also have the following additional technical features:
[0009] In some embodiments, the high entropy alloy aerogel includes at least five metal elements of sodium, potassium, calcium, lead, cerium, magnesium, aluminum, zinc, strontium, barium, copper or cobalt.
[0010] In some embodiments, the solid electrolyte includes at least one of a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte or a polymer solid electrolyte.
[0011] In some embodiments, the coating further comprises a binder; the binder comprises at least one of polyvinylidene fluoride, polyacrylate, polyimide, polyperfluoroalkoxy, polytetrafluoroethylene, polyacrylonitrile or polyvinyl alcohol.
[0012] In some of the embodiments, in the composite material, the mass ratio of the high entropy alloy aerogel to the solid electrolyte is (70-90): (10-16).
[0013] In some of the embodiments, the mass ratio of the high entropy alloy aerogel, the solid electrolyte and the binder is (70-90): (10-16): (8-11).
[0014] In some embodiments, the base film includes at least one of a polyester film, a polyethylene film, or a polypropylene film.
[0015] In some embodiments, the base film has a thickness of 7 to 9 μm and a porosity of 30% to 40%.
[0016] In some embodiments, the coating has a thickness of 3 to 5 μm.
[0017] According to another aspect of the present application, an embodiment of the present application provides a method for preparing a composite diaphragm, the method comprising:
[0018] Dissolving the metal salt in a solvent and adding a thickener to obtain a sol solution;
[0019] The sol solution is mixed with a solid electrolyte, and the pH value of the system is adjusted to alkaline to obtain a composite gel;
[0020] Post-processing the composite gel to obtain a composite material comprising a high entropy alloy aerogel and a solid electrolyte;
[0021] coating a slurry containing the composite material on at least one surface of a base film to obtain a composite diaphragm;
[0022] The post-treatment process method includes at least one of a heat treatment process, a freeze-thaw cycle process, a chemical vapor deposition process, a physical vapor deposition process or an electrodeposition process.
[0023] In some embodiments, the metal salt comprises a mixture of at least five metal salts.
[0024] In some embodiments, the metal salt includes a mixture of at least five of sodium salt, potassium salt, calcium salt, lead salt, cerium salt, magnesium salt, aluminum salt, zinc salt, strontium salt, barium salt, copper salt or cobalt salt.
[0025] In some embodiments, the anion in the metal salt includes at least one of a nitrate ion, an acetate ion or a sulfate ion.
[0026] In some of the embodiments, the solvent includes alcohol and water.
[0027] In some embodiments, the volume ratio of the alcohol to water is 1:(3-4).
[0028] In some embodiments, the alcohol includes one or two of methanol, ethanol, propanol, isopropanol, and propylene glycol.
[0029] In some embodiments, the thickener includes one of polyethylene glycol, polybutylene glycol, polyvinyl alcohol or polyamide alcohol.
[0030] In some embodiments, based on the mass of the solvent, the mass of the metal salt accounts for 35% to 45% of the mass of the solvent.
[0031] In some embodiments, based on the mass of the solvent, the mass of the thickener accounts for 1.5% to 2% of the mass of the solvent.
[0032] In some embodiments, the solid electrolyte includes at least one of a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte or a polymer solid electrolyte.
[0033] In some embodiments, based on the mass of the solvent, the mass of the solid electrolyte accounts for 5% to 8% of the mass of the solvent.
[0034] In some embodiments, the base used to adjust the pH value of the system includes one or more of aluminum hydroxide, copper hydroxide, zinc hydroxide, ammonia water, and sodium carbonate.
[0035] In some embodiments, the pH value of the adjustment system is in the range of 9-11.
[0036] In some of the embodiments, the heat treatment process is carried out in an inert gas atmosphere, the heating rate of the heat treatment is 5-8°C / min, the holding temperature of the heat treatment is 800-1000°C, and the holding time of the heat treatment is 3h-5h.
[0037] In some of the embodiments, after obtaining the composite gel and before the post-treatment, a drying step is also included.
[0038] In some of the embodiments, the slurry containing the composite material includes the composite material, a binder and water.
[0039] In some of the embodiments, in the slurry, the mass ratio of the composite material, the binder and water is (30-40): (3-6):100.
[0040] According to another aspect of the present application, an embodiment of the present application provides a battery, including a diaphragm, wherein the diaphragm is the aforementioned composite diaphragm or a composite diaphragm prepared by the aforementioned preparation method.
[0041] Implementing the technical solution of the present invention has at least the following beneficial effects:
[0042] (1) In the embodiments of the present application, the provided composite diaphragm contains high entropy alloy aerogel, wherein the internal lattice distortion of the high entropy alloy aerogel material is serious. The thermal performance of the diaphragm can be significantly improved by increasing phonon scattering, and the three-dimensional network structure of the high entropy alloy aerogel gives the composite diaphragm good flexibility. Therefore, the composite diaphragm can effectively improve the overall thermal stability of the battery, thereby improving the high temperature performance of the battery.
[0043] (2) The composite membrane also contains a solid electrolyte. The solid electrolyte and the high entropy alloy aerogel can play a synergistic role. For example, the solid electrolyte is dispersed inside the three-dimensional skeleton of the high entropy alloy aerogel. While adjusting the microstructural morphology of the material to form a uniform pore structure, the composite material can form a three-dimensional network structure with a higher specific surface area and a more uniform void structure. It also improves the efficiency of grain boundary ion transmission, thereby improving the electrical performance of the battery.
[0044] (3) In the examples of the present application, a solid electrolyte / high entropy alloy aerogel coating is prepared by a sol-gel method, and after coating it on both sides of the base film, a composite diaphragm with excellent comprehensive performance is obtained by drying at normal pressure. Compared with similar diaphragm coating materials, the multifunctional diaphragm coating prepared by the present invention has a more uniform and stable structure, and after being coated on the surface of the lithium battery diaphragm, it has a significant improvement on the high temperature performance and cycle stability of the battery.
[0045] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 Shown is a SEM image of the surface of the composite diaphragm provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0047] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.
[0048] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0049] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0050] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0051] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0052] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0053] In the related art, some diaphragms include a base film and a coating disposed on the base film, and the coating can increase the puncture strength and high temperature resistance of the diaphragm. However, the existing diaphragm coatings still have problems such as poor thermal performance and unstable interface. For example, the existing diaphragm coatings have a high thermal shrinkage rate and a low melting and breaking temperature, resulting in poor high temperature resistance or thermal performance of the diaphragm.
[0054] In view of this, an embodiment of the present application provides a composite diaphragm, which includes a base film, and a coating disposed on at least one side surface of the base film along a thickness direction;
[0055] The coating includes a composite material, and the composite material includes a high entropy alloy aerogel and a solid electrolyte.
[0056] The provided composite separator has a multi-layer structure, which includes a base film and a coating layer which are stacked.
[0057] The above-mentioned "the coating is disposed on at least one side surface of the base film along the thickness direction" means that the coating can be disposed on one surface of the base film along its own thickness direction, or on two surfaces of the base film along its own thickness direction. The "surface" here can be the entire area of the base film, or a partial area of the base film. For example, in this embodiment, the surface can be the entire area of the base film. This application has no particular limitation on this, as long as the purpose of this application can be achieved.
[0058] As an example, the base film has two surfaces opposite to each other in its thickness direction, and the coating is disposed on the two opposite surfaces of the base film. It is understood that in other embodiments, the coating can also be laminated on any one of the two surfaces of the base film.
[0059] Particularly prominent is that in the composite diaphragm of the embodiment of the present application, the coating of the composite diaphragm contains high entropy alloy aerogel and solid electrolyte, and the high entropy alloy aerogel and solid electrolyte can form a composite material, wherein the internal lattice distortion of the high entropy alloy aerogel material is serious, and the thermal performance of the diaphragm can be significantly improved by increasing phonon scattering, and the three-dimensional network structure of the high entropy alloy aerogel gives the composite diaphragm good flexibility, therefore, the composite diaphragm can effectively improve the overall thermal stability and structural stability of the battery. In addition, the solid electrolyte contained is dispersed inside the three-dimensional skeleton of the high entropy alloy aerogel, and while adjusting the microstructural morphology of the material to form a uniform pore structure, the composite material can be formed into a three-dimensional network structure with a higher specific surface area and a more uniform void structure, and the efficiency of grain boundary ion transmission is also improved, thereby improving the electrical performance of the battery.
[0060] In the present application, the provided composite membrane has a low thermal shrinkage rate and a high melting and breaking temperature under the synergistic effect of the above-mentioned high entropy alloy aerogel and solid electrolyte, so that the composite membrane has excellent high temperature resistance or thermal performance; and the thermal conductivity of the composite membrane is high, which can avoid local high temperature inside the battery, thereby helping to improve the thermal performance of the battery and improve the safety of the battery.
[0061] Based on this, in the composite membrane of the present application, by including high entropy alloy aerogel in the coating of the composite membrane, the good flexibility of the high entropy alloy aerogel is utilized to make the structure of the composite membrane more uniform and stable, and the high entropy alloy aerogel material itself has severe internal lattice distortion, which can effectively improve the thermal performance of the composite membrane; at the same time, by adding solid electrolytes to the composite membrane coating, the grain boundary ion transport can be improved, thereby reducing the battery's charge and discharge internal resistance and improving the battery's long-term cycle performance.
[0062] The term "high entropy alloy" generally refers to an alloy material formed by mixing five or more metal elements in an equimolar ratio or a nearly equimolar ratio. The alloy formed by the composite of at least five metal elements has better tensile strength, corrosion resistance, oxidation resistance and other properties. At the same time, aerogel, as a three-dimensional porous material, has attracted much attention due to its unique structural characteristics. For example, aerogel can be used as an excellent heat-resistant material with a light weight. Therefore, "high entropy alloy aerogel" mainly refers to an alloy material in the form of aerogel and formed by mixing five or more metal elements in an equimolar ratio or a nearly equimolar ratio. Due to the different reduction potentials and nucleation / growth kinetics of different component metals, the use of high entropy alloy aerogel materials of five or more elements can combine the excellent mechanical properties or physicochemical properties of high entropy alloys with the good thermal properties exhibited by the porous characteristics of aerogels.
[0063] It should be noted that the present application does not limit the types of high entropy alloy aerogel and solid electrolyte, as long as the high entropy alloy aerogel and solid electrolyte can be mixed evenly and can be used to prepare the diaphragm coating. Optionally, the high entropy alloy aerogel and solid electrolyte in the present application can be selected from the high entropy alloy aerogel and solid electrolyte materials listed below.
[0064] In some embodiments, the high entropy alloy aerogel includes, but is not limited to, at least five metal elements of sodium, potassium, calcium, lead, cerium, magnesium, aluminum, zinc, strontium, barium, copper or cobalt. For example, the high entropy alloy aerogel may include all metals of sodium, potassium, calcium, lead, cerium, magnesium, aluminum, zinc, strontium, barium, copper or cobalt; the high entropy alloy aerogel includes six metal elements of sodium, potassium, calcium, lead, cerium, magnesium, aluminum, zinc, strontium, barium, copper or cobalt; preferably, the high entropy alloy aerogel includes any five metal elements of sodium, potassium, calcium, lead, cerium, magnesium, aluminum, zinc, strontium, barium, copper or cobalt. At the same time, the molar ratio of each metal element in the high entropy alloy aerogel is equal.
[0065] By selecting the above-mentioned high entropy alloy aerogel as the component material of the composite diaphragm coating, due to the highly disordered mixing of atoms in the high entropy alloy aerogel, that is, the serious lattice distortion inside the high entropy alloy aerogel material, the thermal performance of the diaphragm can be significantly improved by increasing phonon scattering, such as reducing the thermal shrinkage rate, increasing the melting and breaking temperature, and increasing the thermal conductivity of the diaphragm, avoiding local high temperature inside the battery, and thus helping to improve the thermal stability and safety of the battery. At the same time, the high entropy alloy aerogel also has a three-dimensional network structure, which can improve the flexibility of the composite diaphragm and improve the structural stability of the battery.
[0066] It should be noted that the molar ratio of the metal elements in the high entropy alloy aerogel material is equal or approximately equal, otherwise a material with a highly disordered atomic mixture cannot be formed, and the heat resistance of the final composite diaphragm will be poor.
[0067] Therefore, by making the molar ratio of each metal element in the high entropy alloy aerogel the same, the structural stability can be enhanced. For example, equimolar mixing helps to eliminate the dominant effect of any element, promotes the uniform distribution of elements, and forms a more complex atomic arrangement structure with a high degree of mixing, thereby improving the overall structural stability of the material. It can also promote multiple interactions. For example, by doping different metal ions in equimolar ratios, rich interfaces and interfacial interactions can be induced, including electrostatic interactions and coordination interactions between metal ions, which are conducive to forming a tighter network structure and improving the mechanical strength and thermal stability of the aerogel. In addition, the high entropy effect can lead to unique physicochemical properties, such as enhanced conductivity and optimized catalytic activity; the combination of equimolar ratios can maximize this effect, making the material exhibit novel properties different from traditional single components or simple mixtures. In addition, in a multi-component system, different components tend to phase separate to reach the lowest energy state, while equimolar ratios can effectively inhibit phase separation and maintain the single phase structure of the material, which is crucial to maintaining the nanoporous structure of the aerogel.
[0068] In some embodiments, the solid electrolyte includes, but is not limited to, at least one of a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, or a polymer solid electrolyte. Specifically, the sulfide solid electrolyte may be selected from one or more of a LISICON type sulfide solid electrolyte, an LGPS type sulfide solid electrolyte, or a argyrodite type solid electrolyte; the oxide solid electrolyte may be selected from one or more of a garnet type oxide, a perovskite type oxide, a sodium superion conductor (NASICON) type oxide, or a argyrodite type oxide; the halide solid electrolyte may be selected from one or more of a lithium halide, a mixed halide, or a composite halide; the polymer solid electrolyte may be selected from one or more of polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, polycarbonate, polyvinyl alcohol, polyacrylic acid, polyimide, polyurethane, or polysiloxane.
[0069] The above-mentioned solid electrolyte can be well dispersed inside the three-dimensional skeleton of the high-entropy alloy aerogel. While adjusting the microstructural morphology of the material to form a uniform pore structure, it can enable the composite material to form a three-dimensional network structure with a higher specific surface area and a more uniform void structure. It also improves the grain boundary ion transmission efficiency, thereby improving the electrical performance of the battery.
[0070] In some embodiments, the coating further comprises a binder; the binder comprises, but is not limited to, at least one of polyvinylidene fluoride, polyacrylate, polyimide, polyperfluoroalkoxy (PFA), polytetrafluoroethylene, polyacrylonitrile or polyvinyl alcohol.
[0071] In the present application, the coating may be mainly composed of a composite material and a binder, and the binder may be used to improve the adhesion between the composite material and the base film and improve the bonding effect. The specific type of the binder is not limited to the substances listed above, and other materials that can be used to improve the adhesion do not limit the purpose of the present invention, and other similar bonding materials may also be used in the present invention.
[0072] In some embodiments, in the composite material, the mass ratio of high entropy alloy aerogel to solid electrolyte is (70-90): (10-16); as an example, the mass ratio of high entropy alloy aerogel to solid electrolyte can be 70:10, 75:12, 78:15, 79:13, 80:11, 85:13, 86:15, 88:14, 89:12, 90:16, etc.
[0073] In some embodiments, the mass ratio of high entropy alloy aerogel, solid electrolyte and binder is (70-90):(10-16):(8-11); as an example, the mass ratio of high entropy alloy aerogel, solid electrolyte and binder can be 70:10:8, 75:12:9, 78:15:10, 79:13:11, 80:11:11, 85:13:10, 86:15:9, 88:14:8, 89:12:10, 90:16:11, etc.
[0074] It is understandable that the mass ratio of high entropy alloy aerogel, solid electrolyte and binder affects the final thermal performance, structural stability and conductivity of the composite diaphragm. By controlling the mass ratio of each substance in the diaphragm coating within the above range, the role of high entropy alloy aerogel, solid electrolyte and other materials in combination can be fully utilized to effectively improve the performance of the composite diaphragm. For example, if the amount of solid electrolyte added is lower than the above mass ratio range, the internal resistance of the battery charge and discharge will increase and the battery cycle performance will be reduced; however, when the amount of solid electrolyte added exceeds the above ratio range, the permeability of the composite diaphragm will decrease, further affecting the transmission of lithium ions, and will also increase the internal resistance of the battery charge and discharge, thereby reducing the battery cycle stability.
[0075] In some embodiments, the base film includes at least one of a polyester film, a polyethylene film, or a polypropylene film. As an example, the base film can be a polyester film, a polyethylene film, a polypropylene film, or a composite film composed of polyethylene and polypropylene.
[0076] In some embodiments, the thickness of the base film is 7 to 9 μm, and the porosity is 30% to 40%; as an example, the thickness of the base film may be 7 μm, 7.5 μm, 8 μm, 8.5 μm, or 9 μm, and of course it may be other values within the above range, which is not limited here; the porosity of the base film may be 30%, 31%, 33%, 35%, 36%, 37%, 38%, 39%, or 40%, and of course it may be other values within the above range, which is not limited here.
[0077] First, by limiting the thickness of the base film within the above range, the composite diaphragm can meet the mechanical strength requirements (can resist certain physical stress and dendrite growth) while not significantly reducing the ion conductivity, so that the battery maintains a low internal resistance and does not have a significant negative impact on the battery's charge and discharge efficiency and power output. Second, by limiting the porosity of the base film within the above range, the composite diaphragm can absorb more electrolyte, thereby improving the uniformity of the electrolyte distribution in the battery, which helps to improve the battery's ion conductivity and overall electrochemical performance; at the same time, when the base film porosity is within this range, the mechanical strength of the composite diaphragm will not be too low, and it is not easy to be damaged during battery use or assembly.
[0078] In some embodiments, the thickness of the coating is 3 to 5 μm; as an example, the thickness of the coating can be 3 μm, 3.5 μm, 3.6 μm, 4 μm, 4.5 μm, 5 μm, etc., and of course it can also be other values within the above range, which are not limited here. If the coating thickness is less than 3 μm, the heat resistance of the composite diaphragm will be limited, and the thermal stability, structural stability and electrical performance of the battery will be difficult to further ensure and optimize, which is not conducive to the long cycle of the battery; if the coating thickness is higher than 5 μm, the transmission efficiency of electrons will increase, the internal resistance of the battery will increase, and the rate performance of the battery will be further affected.
[0079] Thus, based on the above scheme, a composite diaphragm is provided. By setting a coating on the surface of at least one side of the base film along the thickness direction, the existing diaphragm coating has the problems of poor thermal performance and unstable interface. The coating of the composite diaphragm includes high entropy alloy aerogel and solid electrolyte, wherein the internal lattice distortion of the high entropy alloy aerogel material is serious, and the thermal performance of the diaphragm can be significantly improved by increasing phonon scattering, and the three-dimensional network structure of the high entropy alloy aerogel gives the composite diaphragm good flexibility, therefore, the composite diaphragm can effectively improve the overall thermal stability and structural stability of the battery, and improve the safety of the battery; and the solid electrolyte in the coating can be well dispersed inside the three-dimensional skeleton of the high entropy alloy aerogel, while adjusting the microstructural morphology of the material to form a uniform pore structure, the composite material can form a three-dimensional network structure with a higher specific surface area and a more uniform void structure, and also improve the grain boundary ion transmission efficiency, thereby improving the electrical performance of the battery.
[0080] Based on the same inventive concept, the present application also provides a method for preparing a composite diaphragm, the method comprising:
[0081] Dissolving the metal salt in a solvent and adding a thickener to obtain a sol solution;
[0082] The sol solution is mixed with a solid electrolyte, and the pH value of the system is adjusted to alkaline to obtain a composite gel;
[0083] The composite gel is post-processed to obtain a composite material comprising a high entropy alloy aerogel and a solid electrolyte;
[0084] coating a slurry containing a composite material on at least one surface of a base film to obtain a composite diaphragm;
[0085] The post-processing process includes at least one of a heat treatment process, a freeze-thaw cycle process, a chemical vapor deposition process, a physical vapor deposition process or an electrodeposition process.
[0086] In this application, the excellent performance of high entropy aerogel and solid electrolyte is comprehensively utilized, and the sol-gel method is adopted to prepare a coating containing solid electrolyte and high entropy alloy aerogel, which is coated on both sides of the base film and dried at normal pressure to obtain a composite diaphragm with excellent comprehensive performance. The prepared multifunctional diaphragm coating structure is more uniform and stable, and after being coated on the surface of the lithium battery base film, it has a significant improvement effect on the high temperature performance and electrical performance of the battery. The method provided in this application has low preparation cost and simple process, and meets the technical requirements for industrialization.
[0087] It should be understood that all the features and advantages described above for the "composite diaphragm" are also applicable to the "method for preparing the composite diaphragm", and will not be described in detail here.
[0088] In some specific embodiments, the method for preparing the composite membrane specifically comprises the following steps (a) to (b):
[0089] (a) Preparation of composite materials.
[0090] In step (a), preparing the composite material includes: weighing a certain amount of metal salt, adding the metal salt to the solvent, stirring at room temperature until it is completely dissolved to form a transparent solution. Subsequently, slowly adding an appropriate amount of thickener (such as a polymer thickener) to help form a more uniform gel network to obtain a sol solution. Then, adding a solid electrolyte to the sol solution, stirring until it is evenly dispersed, slowly dripping a weak base into the mixed sol solution, monitoring the pH value while dripping, until the solution is a strong alkaline, forming a composite gel. Then, the obtained composite gel is dried and post-treated to obtain a composite material. Among them, the post-treatment can be one or more of a heat treatment process, a cyclic freeze-thaw process, a chemical vapor deposition process, a physical vapor deposition process or an electrodeposition process. Preferably, the post-treatment is performed by heat treatment. In some embodiments, in step (a), the above-mentioned metal salt can be a mixture of at least five metal salts, wherein the molar ratio of the five metal salts is equal. For example, weighing a certain amount of metal salt means weighing five or more metal salts (such as metal nitrates) in equal molar ratios.
[0091] In some embodiments, the metal salt includes, but is not limited to, a mixture of at least five of sodium salt, potassium salt, calcium salt, lead salt, cerium salt, magnesium salt, aluminum salt, zinc salt, strontium salt, barium salt, copper salt, or cobalt salt.
[0092] In some embodiments, the anion in the metal salt includes at least one of a nitrate ion, an acetate ion or a sulfate ion. That is, the metal salt can be a metal nitrate, a metal acetate or a metal sulfate.
[0093] Exemplarily, the metal salt is preferably a metal nitrate, and the metal nitrate may be any five of sodium nitrate, potassium nitrate, calcium nitrate, lead nitrate, cerium nitrate, magnesium nitrate, aluminum nitrate, zinc nitrate, strontium nitrate, barium nitrate, copper nitrate, and cobalt nitrate.
[0094] In some embodiments, the solvent includes alcohol and water, wherein the volume ratio of alcohol to water is 1:(3-4); as an example, the volume ratio of alcohol to water can be 1:3, 1:3.2, 1:3.5, 1:3.8, 1:4, etc., and of course it can also be other values within the above range, which is not limited here.
[0095] In some embodiments, the alcohol includes, but is not limited to, one or two of methanol, ethanol, propanol, isopropanol, and propylene glycol.
[0096] In some embodiments, the thickener may be a polymer thickener, which includes, but is not limited to, at least one of polyethylene glycol, polybutylene glycol, polyvinyl alcohol, or polyamide alcohol.
[0097] In some embodiments, based on the mass of the solvent, the mass of the metal salt accounts for 35% to 45% of the mass of the solvent; that is, the total amount of the metal salt added is 35% to 45% of the mass of the solvent. As an example, the mass of the metal salt can be 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, etc. of the mass of the solvent, and of course it can also be other values within the above range, which is not limited here.
[0098] In some embodiments, based on the mass of the solvent, the mass of the thickener accounts for 1.5% to 2% of the mass of the solvent; that is, the amount of the thickener added accounts for 1.5% to 2% of the mass of the solvent. As an example, the mass of the thickener can be 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, etc. of the mass of the solvent, and of course it can also be other values within the above range, which is not limited here.
[0099] By limiting the type and amount of thickener, after post-processing (such as heat treatment), the thickener will decompose, and the high entropy alloy aerogel material will eventually form a porous structure. The diaphragm formed after coating can retain a certain air permeability, so that the battery has a smaller charge and discharge internal resistance. At the same time, the composite diaphragm has a certain air permeability, which can also ensure the smooth transmission of lithium ions, improve the utilization efficiency of active substances in the battery, and thus improve the cycle performance of the battery. It should be noted that too little thickener will make it difficult to form a uniform three-dimensional network gel structure, and too much thickener will make the sol too viscous, which is not conducive to the uniform dispersion of the solid electrolyte.
[0100] In some embodiments, the solid electrolyte includes at least one of a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, or a polymer solid electrolyte. It should be noted that the heat treatment in the post-processing process may cause some solid electrolyte materials that are not resistant to high temperatures to decompose. Therefore, when the post-processing process uses heat treatment, a high-temperature resistant oxide solid electrolyte, such as lithium aluminum titanium phosphate (LATP) solid electrolyte, will be selected.
[0101] In some embodiments, in order to achieve the mixing of high entropy alloy aerogel preparation and solid electrolyte, when the post-treatment process is a cyclic freeze-thaw method, a chemical vapor deposition method, a physical vapor deposition method, or an electrodeposition method, the solid electrolyte that can be selected in these methods may include a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte, or a halide solid electrolyte.
[0102] In some embodiments, based on the mass of the solvent, the mass of the solid electrolyte accounts for 5% to 8% of the mass of the solvent; as an example, the mass of the solid electrolyte can be 5%, 6%, 7%, 8% of the mass of the solvent, etc., and of course it can also be other values within the above range, which are not limited here. By limiting the amount of solid electrolyte to the above range, the battery can ultimately have better cycle stability. Specifically, if the amount of solid electrolyte added is lower than the above mass ratio range, the internal resistance of the battery charge and discharge will increase, and the battery cycle performance will be reduced; however, when the amount of solid electrolyte added exceeds the above ratio range, the permeability of the composite diaphragm will decrease, further affecting the transmission of lithium ions, and will also increase the internal resistance of the battery charge and discharge, thereby reducing the battery cycle stability.
[0103] In some embodiments, the base used to adjust the pH value of the system includes, but is not limited to, one or more of aluminum hydroxide, copper hydroxide, zinc hydroxide, ammonia water, and sodium carbonate.
[0104] In some embodiments, the pH value of the adjustment system is in the range of 9 to 11; as an example, the pH value of the adjustment system can be 9, 10, 11, etc., and of course can be other values within the above range, which is not limited here.
[0105] In some embodiments, drying can be one of atmospheric pressure drying, freeze drying, and supercritical drying; preferably, atmospheric pressure drying is used for drying. Specifically, the temperature of atmospheric pressure drying is 60-80°C, such as the drying temperature can be 60°C, 65°C, 66°C, 70°C, 80°C, etc., and of course it can also be other values within the above range, which is not limited here; the air flow rate is 3.5-5m / s, such as the air flow rate can be 3.5m / s, 3.6m / s, 4m / s, 4.5m / s, 5m / s, etc., and of course it can also be other values within the above range, which is not limited here; the drying time is 30min-40min, such as the drying time can be 30min, 32min, 33min, 35min, 36min, 38min, 39min, 40min, etc., and of course it can also be other values within the above range, which is not limited here.
[0106] In some embodiments, post-treatment adopts a heat treatment process, which is carried out in an inert gas atmosphere (it can be any inert gas), and the heating rate of the heat treatment is 5-8°C / min. As an example, the heating rate of the heat treatment can be 5°C / min, 6°C / min, 7°C / min, 8°C / min, etc., and of course it can also be other values within the above range, which is not limited here; the holding temperature of the heat treatment is 800-1000°C. As an example, the holding temperature of the heat treatment can be 800°C, 830°C, 850°C, 900°C, 990°C, 1000°C, etc., and of course it can also be other values within the above range, which is not limited here; the holding time of the heat treatment is 3h-5h. As an example, the holding time of the heat treatment can be 3h, 3.5h, 4h, 4.5h, 5h, etc., and of course it can also be other values within the above range, which is not limited here.
[0107] (b) Preparation of composite membrane.
[0108] In step (b), preparing the composite diaphragm includes: dispersing the composite material obtained in step (a) and a binder in an aqueous solution to form a diaphragm slurry, coating the diaphragm slurry on both sides of a base membrane (such as a polymer diaphragm), and drying at normal pressure to obtain a composite diaphragm.
[0109] In some embodiments, in step (b), the slurry containing the composite material, that is, the membrane slurry includes the composite material, a binder and water.
[0110] In some embodiments, the mass ratio of the composite material, the binder and the water in the diaphragm slurry is (30-40): (3-6): 100; as an example, the mass ratio of the composite material, the binder and the water in the slurry can be 30:3:100, 32:3:100, 30:5:100, 35:4:100, 38:6:100, 39:5:100, 40:4:100, etc., and of course it can also be other values within the above range, which is not limited here.
[0111] Optionally, the binder is one or more of polyvinylidene fluoride, polyacrylate, polyimide, polyperfluoroalkoxy, polytetrafluoroethylene, polyacrylonitrile, and polyvinyl alcohol.
[0112] In some embodiments, the coating method of the diaphragm slurry includes one of spray coating, dip coating, and transfer coating.
[0113] Optionally, the base film includes at least one of a polyester film, a polyethylene film or a polypropylene film; the base film has a thickness of 7 to 9 μm and a porosity of 30% to 40%.
[0114] Optionally, the single-sided coating thickness is 3 to 5 μm.
[0115] In some embodiments, in step (b), the atmospheric pressure drying temperature is 60-80° C., the air flow rate is 3.5-5 m / s, and the drying time is 30-40 min.
[0116] Thus, based on the above, the present invention mixes a variety of metal compounds in a specific proportion, prepares a gel coating by a sol-gel method, and combines atmospheric pressure drying to form a heat-resistant coating containing a high entropy alloy aerogel and a solid electrolyte on both sides of the base film. Among them, the internal lattice distortion of the high entropy alloy aerogel material is serious, and the thermal performance of the diaphragm can be significantly improved by increasing phonon scattering, and the three-dimensional network structure of the aerogel gives the diaphragm good flexibility. At the same time, an appropriate amount of solid electrolyte is dispersed inside the three-dimensional skeleton of the high entropy alloy aerogel, and while adjusting the microstructure morphology of the material, the grain boundary ion transport is improved to improve the electrical performance of the battery. Compared with conventional diaphragms, the multifunctional diaphragm coating structure prepared by the present invention is more uniform and stable, and after being coated on the surface of the lithium battery diaphragm, the high temperature performance and electrical performance of the battery are significantly improved. Furthermore, by applying it in a battery, the thermal performance of the diaphragm can be significantly enhanced, the overall thermal stability of the battery can be effectively improved, and the safety of the battery can be improved.
[0117] Based on the same inventive concept, an embodiment of the present application further provides a battery, comprising a diaphragm, wherein the diaphragm is the aforementioned composite diaphragm or a composite diaphragm prepared by the aforementioned preparation method.
[0118] Since the battery includes the composite diaphragm provided in the embodiment of the present application, it has relatively excellent thermal stability and structural stability, and has a lower battery charge and discharge internal resistance and good cycle stability.
[0119] In some embodiments, the battery may be a lithium-ion battery. The battery stacking type may be, for example, a wound or laminated battery, and the structure type may be, for example, a square shell (aluminum shell, steel shell, etc.) battery, a soft pack battery, or a cylindrical battery, etc., without specific limitation, and the battery has excellent high temperature performance and electrical performance.
[0120] In some embodiments, the battery further comprises a positive electrode sheet, an electrolyte and a negative electrode sheet, that is, the battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a composite separator.
[0121] In this embodiment, there is no limitation on the materials and structures of the positive electrode sheet, the positive current collector, the conductive agent, the binder in the positive active material layer, and the like, and any positive electrode sheet structure and composition known in the art that can be used for secondary batteries can be selected.
[0122] In this embodiment, there is no limitation on the materials and structures of the negative electrode sheet, the negative current collector, the conductive agent, the binder in the negative active material layer, and the like, and the positive electrode sheet structure and components known in the art that can be used for secondary batteries can be selected.
[0123] It should also be noted that the battery of the present application is not limited to the specific material or type of the electrolyte, and the components and types that are known in the art and can be used for secondary batteries can be selected as long as the purpose of the present application can be achieved.
[0124] Since the battery provided in the embodiment of the present invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0125] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this area or the product instructions are used. If the manufacturer of the reagents, materials or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0126] Example 1
[0127] Weigh 42.5g sodium nitrate, 50.5g potassium nitrate, 94g copper nitrate, 82g calcium nitrate, and 128g magnesium nitrate, add the five metal nitrates to 1L of ethanol / water (the volume ratio of ethanol to water is 1:4) mixed solution, and then add 15g polyethylene glycol, stir until completely dissolved at room temperature to form a sol solution. Then, add 54.6g of lithium titanium aluminum phosphate solid electrolyte to the sol solution, stir until it is evenly dispersed, and slowly drip ammonia water into the mixed sol solution, while monitoring the pH value while dripping, until the pH value of the solution reaches 10, forming a composite gel. The composite gel is dried at normal pressure to obtain a composite aerogel, wherein the normal pressure drying conditions are: drying temperature 70℃, air flow rate 4m / s, and drying time 35min. Finally, the composite aerogel is heated to 900℃ at a heating rate of 6℃ / min under nitrogen, and the solid electrolyte / high entropy alloy aerogel composite material is obtained after keeping the temperature for 4h. 1.4 kg of the prepared composite material and 0.2 kg of polyvinylidene fluoride binder were added to 4 kg of water, and mechanically stirred until uniformly dispersed to form a diaphragm slurry. The diaphragm slurry was sprayed on both sides of a 9 μm polyethylene diaphragm with a porosity of 35% and a single-sided coating thickness of 4 μm. Finally, after drying at normal pressure, a solid electrolyte / high entropy alloy aerogel-coated composite diaphragm was obtained, wherein the mass ratio of the solid electrolyte to the high entropy alloy aerogel in the composite diaphragm was 80:11.
[0128] Embodiment 2:
[0129] Weigh 42.5g sodium nitrate, 50.5g potassium nitrate, 94g copper nitrate, 82g calcium nitrate, and 128g magnesium nitrate, add the five metal nitrates to 1L of ethanol / water (the volume ratio of ethanol to water is 1:3.5) mixed solution, and then add 15g polyethylene glycol, stir until completely dissolved at room temperature to form a sol solution. Then, add 60.7g lithium phosphorus sulfur chloride solid electrolyte to the sol solution, stir until it is evenly dispersed, and slowly add ammonia water to the mixed sol solution, while monitoring the pH value while adding, until the pH value of the solution reaches 9, forming a composite gel. The composite gel is dried at normal pressure to obtain a composite aerogel, wherein the normal pressure drying conditions are: drying temperature 70℃, air flow rate 4m / s, and drying time 35min. Finally, the composite aerogel is heated to 900℃ at a heating rate of 6℃ / min under nitrogen, and the solid electrolyte / high entropy alloy aerogel composite material is obtained after keeping the temperature for 4h. 1.4 kg of the prepared composite material and 0.2 kg of polyvinylidene fluoride binder were added to 4 kg of water, and mechanically stirred until uniformly dispersed to form a diaphragm slurry. The diaphragm slurry was sprayed on both sides of a 9 μm polyethylene diaphragm with a porosity of 30% and a single-sided coating thickness of 3 μm. Finally, after drying at normal pressure, a solid electrolyte / high entropy alloy aerogel-coated composite diaphragm was obtained, wherein the mass ratio of the solid electrolyte to the high entropy alloy aerogel in the composite diaphragm was 85:13.
[0130] Embodiment 3:
[0131] Weigh 42.5g sodium nitrate, 50.5g potassium nitrate, 94g copper nitrate, 82g calcium nitrate, and 128g magnesium nitrate, add the five metal nitrates to 1L of ethanol / water (the volume ratio of ethanol to water is 1:4) mixed solution, and then add 17g polyethylene glycol, stir until completely dissolved at room temperature to form a sol solution. Then, add 54.6g of lithium titanium aluminum phosphate solid electrolyte to the sol solution, stir until it is evenly dispersed, and slowly drip ammonia water into the mixed sol solution, while monitoring the pH value while dripping, until the pH value of the solution reaches 11, forming a composite gel. The composite gel is dried at normal pressure to obtain a composite aerogel, wherein the normal pressure drying conditions are: drying temperature 70℃, air flow rate 4m / s, and drying time 35min. Finally, the composite aerogel is heated to 1000℃ at a heating rate of 8℃ / min under nitrogen, and the solid electrolyte / high entropy alloy aerogel composite material is obtained after being kept warm for 3h. 1.4 kg of the prepared composite material and 0.2 kg of polyvinylidene fluoride binder were added to 4 kg of water, and mechanically stirred until uniformly dispersed to form a diaphragm slurry. The diaphragm slurry was sprayed on both sides of a 7 μm polyethylene diaphragm with a porosity of 40% and a single-sided coating thickness of 4.5 μm. Finally, after drying at normal pressure, a solid electrolyte / high entropy alloy aerogel-coated composite diaphragm was obtained, in which the mass ratio of the solid electrolyte to the high entropy alloy aerogel in the composite diaphragm was 80:11.
[0132] Embodiment 4:
[0133] Weigh 42.5g sodium nitrate, 50.5g potassium nitrate, 94g copper nitrate, 82g calcium nitrate, 128g magnesium nitrate, and 182.5g strontium nitrate, add the six metal nitrates to 1.5L of ethanol / water (the volume ratio of ethanol to water is 1:4) mixed solution, and then add 28g polyethylene glycol, stir until completely dissolved at room temperature to form a sol solution. Then, add 90.7g of lithium titanium aluminum phosphate solid electrolyte to the sol solution, stir until it is evenly dispersed, and slowly drip ammonia water into the mixed sol solution, while monitoring the pH value while dripping, until the pH value of the solution reaches 10, forming a composite gel. The composite gel is dried at normal pressure to obtain a composite aerogel, wherein the normal pressure drying conditions are: drying temperature 70℃, air flow rate 4m / s, and drying time 35min. Finally, the composite aerogel is heated to 900℃ at a heating rate of 6℃ / min under nitrogen, and the solid electrolyte / high entropy alloy aerogel composite material is obtained after keeping the temperature for 4h. 1.2 kg of the prepared composite material and 0.12 kg of polytetrafluoroethylene binder were added to 4 kg of water, and mechanically stirred until uniformly dispersed to form a diaphragm slurry. The diaphragm slurry was sprayed on both sides of a 9 μm polypropylene diaphragm, the porosity of the polyethylene diaphragm was 35%, and the single-sided coating thickness was 4 μm. Finally, after drying at normal pressure, a solid electrolyte / high entropy alloy aerogel-coated composite diaphragm was obtained, wherein the mass ratio of the solid electrolyte to the high entropy alloy aerogel in the composite diaphragm was 70:16.
[0134] Embodiment 5:
[0135] Weigh 42.5g sodium nitrate, 50.5g potassium nitrate, 94g copper nitrate, 82g calcium nitrate, and 128g magnesium nitrate, add the five metal nitrates to 1L of ethanol / water (the volume ratio of ethanol to water is 1:4) mixed solution, and then add 18g polyethylene glycol, stir until completely dissolved at room temperature to form a sol solution. Then, add 56.4g of lithium titanium aluminum phosphate solid electrolyte to the sol solution, stir until it is evenly dispersed, and slowly add ammonia water to the mixed sol solution, while monitoring the pH value while adding, until the pH value of the solution reaches 10, forming a composite gel. The composite gel is subjected to supercritical carbon dioxide drying to obtain a composite aerogel, wherein the atmospheric pressure drying conditions are: drying temperature 70℃, air flow rate 4m / s, and drying time 35min. Finally, the composite aerogel is heated to 900℃ at a heating rate of 6℃ / min under nitrogen, and the solid electrolyte / high entropy alloy aerogel composite material is obtained after keeping the temperature for 4h. 1.6 kg of the prepared composite material and 0.2 kg of polyvinylidene fluoride binder were added to 4 kg of water, and mechanically stirred until uniformly dispersed to form a diaphragm slurry. The diaphragm slurry was transferred and coated on both sides of a 9 μm polyethylene diaphragm with a porosity of 35% and a single-sided coating thickness of 4 μm. Finally, after drying at normal pressure, a solid electrolyte / high entropy alloy aerogel-coated composite diaphragm was obtained, in which the mass ratio of solid electrolyte to high entropy alloy aerogel in the composite diaphragm was 80:11.
[0136] Example 6
[0137] The difference between Example 6 and Example 1 is that the metal nitrates added are 42.5 g of sodium nitrate, 50.5 g of potassium nitrate, 106 g of aluminum nitrate, 82 g of calcium nitrate, 128 g of magnesium nitrate, and 182.5 g of strontium nitrate.
[0138] Example 7
[0139] The difference between Example 7 and Example 1 is that the metal nitrates added are 42.5 g of sodium nitrate, 50.5 g of potassium nitrate, 106 g of aluminum nitrate, 82 g of calcium nitrate, 94.7 g of zinc nitrate, and 182.5 g of strontium nitrate.
[0140] Example 8
[0141] The difference between Example 8 and Example 1 is that the solid electrolyte used is Li7La3Zr2O with a garnet structure. 12 .
[0142] Comparative Example 1:
[0143] The difference between Comparative Example 1 and Example 1 is that the amount of sodium nitrate is 55g and the amount of potassium nitrate is 60g, and the rest is the same as Example 1.
[0144] Comparative Example 2:
[0145] The difference between Comparative Example 2 and Example 1 is that polyethylene glycol is not added, and the rest is the same as Example 1.
[0146] Comparative Example 3:
[0147] The difference between Comparative Example 3 and Example 1 is that no lithium aluminum titanium phosphate solid electrolyte is added, and the rest is the same as Example 1.
[0148] Comparative Example 4:
[0149] The difference between Comparative Example 4 and Example 1 is that the amount of lithium aluminum titanium phosphate solid electrolyte used is 120 g, and the rest is the same as Example 1.
[0150] Comparative Example 5:
[0151] The only difference between Comparative Example 5 and Example 1 is that conventional alumina ceramic material is coated on the surface of the polyethylene diaphragm, and the parameters of the thickness, porosity of the polyethylene diaphragm and the coating thickness of the alumina ceramic material are the same as those in Example 1.
[0152] Comparative Example 6:
[0153] The difference between Comparative Example 6 and Example 1 is that the amount of the composite material added to the diaphragm slurry is 1 kg, and the rest is the same as Example 1.
[0154] Performance Testing
[0155] The performance tests of the composite diaphragms prepared in the above embodiments and comparative examples and the constructed lithium batteries were carried out as follows:
[0156] 1. Performance test of composite diaphragm:
[0157] (1) Thickness test: Use a high-precision thickness gauge to test the thickness of the diaphragm at different locations and take the average value of 10 thicknesses.
[0158] (2) Air permeability test: The diaphragm to be tested is placed between two air chambers. Gas is passed from one air chamber through the diaphragm to the other air chamber through a constant pressure difference. The air permeability of the diaphragm is calculated by measuring the amount of gas passing through the diaphragm per unit time.
[0159] (3) Needle puncture strength test: Referring to GB / T 36363-2018 standard, the diaphragm was placed under the sample table fixing fixture, and a universal tensile testing machine was used to record the maximum force value of the 1 mm diameter round needle puncturing the diaphragm at a speed of 100±100 mm / min.
[0160] (4) Heat shrinkage test: Cut the diaphragm into 100 mm*100 mm samples, place the samples flatly between two layers of A4 paper, and then bake the samples in an oven at 130°C for 1 hour. After heating, take out the samples and measure the sample size again.
[0161] Thermal shrinkage rate = (size before shrinkage - size after shrinkage) / size before shrinkage * 100%
[0162] (5) Film rupture temperature test: The diaphragm is cut into appropriate sizes and placed in a hot press. A heating compression test is performed at different temperatures and pressures to test the compressive strength and density of the diaphragm at different temperatures and obtain the film rupture temperature.
[0163] (6) Thermal conductivity test: Place the membrane sample in the thermal conductivity tester to ensure good contact between the sample and the heat source and the cold source. Start the test program and wait for the system to reach a steady state, that is, after the heat flow and temperature distribution are stable, record the key parameters such as heat flow, temperature difference, and sample thickness. Use the recorded data and Fourier's law to calculate the thermal conductivity: λ = Q / (A*ΔT). Where λ is the thermal conductivity, Q is the heat flow, A is the effective area of the sample, and ΔT is the temperature difference on both sides.
[0164] The test results of the composite membranes of various embodiments and comparative examples are shown in Table 1.
[0165] 2.Battery performance test:
[0166] Preparation of lithium-ion batteries
[0167] The negative electrode sheet (the negative electrode active material is graphite), the prepared composite separator, and the positive electrode sheet (the positive electrode active material is lithium nickel cobalt manganese oxide) are stacked in sequence and wound to obtain a bare battery cell. After the tabs are welded, the bare battery cell is placed in a battery aluminum shell / soft-pack aluminum-plastic film. After liquid injection, side top sealing, drying, formation, constant volume, and exhaust sealing, a lithium-ion battery is obtained.
[0168] Conduct electrochemical performance tests on batteries
[0169] (1) Resistance (discharge resistance and charge resistance) test: At room temperature 25°C, the charge resistance and discharge resistance of each lithium battery at 20% SOC were tested using a charge and discharge test cabinet to determine the internal resistance of the lithium battery at low SOC. The test results of each embodiment and comparative example are shown in Table 2.
[0170] (2) Capacity retention rate (25°C and 50°C capacity retention rate) test: At 25°C and 50°C, respectively, charge at a constant current of 1C to 4.25V, and record the charge capacity at this time as the first charge capacity; then charge at a constant voltage of 4.25V until the current decreases to 0.05C, and then discharge at a constant current of 0.1C to 2.8V, and record the discharge capacity at this time as the first discharge capacity. Repeat the above charge and discharge cycle for 300 and 600 cycles, and record the discharge capacity at the 300th and 600th cycles; the capacity retention rate after 300 and 600 cycles can be calculated by the following formula:
[0171] Capacity retention rate at the 300th cycle = discharge capacity at the 300th cycle / first discharge capacity * 100%;
[0172] The capacity retention rate of the 600th cycle = the discharge capacity of the 300th cycle / the first discharge capacity * 100%. The test results of the embodiments and comparative examples are shown in Table 3.
[0173] Table 1
[0174]
[0175] Table 2
[0176]
[0177]
[0178] Table 3
[0179]
[0180] It can be seen from Tables 1-3 that, overall, compared with Comparative Examples 1-6, the solid electrolyte / high entropy alloy aerogel composite materials prepared in Examples 1-8 of the present invention can effectively improve the mechanical properties, air permeability, and temperature resistance of the diaphragm, and improve the charge and discharge internal resistance, long-term cyclability, and high temperature performance of the battery.
[0181] Further, in Table 1, the mechanical properties and temperature resistance of the diaphragms prepared in Examples 1-8 and Comparative Examples 1-6 are compared, and Tables 2 and 3 compare the resistance, high temperature performance and cycle performance of the batteries of Examples 1-8 and Comparative Examples 1-6. In Comparative Example 1, the five metal nitrates are not added in an equimolar mass ratio, and a high entropy alloy material with highly disordered atomic mixing cannot be formed, that is, the non-high entropy alloy aerogel added in Comparative Example 1, so the thermal performance of the diaphragm is poor. For example, in Table 1, through the analysis and comparison of Example 1 and Comparative Example 1, it can be seen that the composite diaphragm of Example 1 of the present invention reduces the thermal shrinkage rate, increases the melting and rupture temperature, and increases the thermal conductivity, which means that Example 1 of the present invention can improve the high temperature resistance or thermal performance of the diaphragm by adopting high entropy alloy aerogel, and can effectively avoid local high temperature inside the battery, thereby improving the thermal performance and safety of the battery; and because the composite diaphragm of Example 1 of the present invention has good thermal properties, it is applied to the battery. It can also be seen from Table 3 that the battery using the composite diaphragm of Example 1 of the present invention has better cycle stability at room temperature (25°C) and high temperature (45°C) than the battery using the composite diaphragm of Comparative Example 1.
[0182] In Comparative Example 2, no polymer thickener is added, which affects the composite material and prevents it from forming an aerogel porous structure. The air permeability of the coated diaphragm is poor, resulting in an increase in the internal resistance of the battery charge and discharge. At the same time, insufficient air permeability of the diaphragm may lead to poor lithium ion transmission, resulting in a decrease in the utilization rate of active substances and a slight decrease in the cycle performance of the battery. In Comparative Example 3, no solid electrolyte is added to the high entropy alloy aerogel, the internal resistance of the battery is large, and the cycle stability is reduced. In Comparative Example 4, an excess of solid electrolyte is added to the high entropy alloy aerogel, the air permeability of the diaphragm is slightly reduced, and the internal resistance and cycle performance are slightly deteriorated. The experimental data of Comparative Examples 3 and 4 show that adding an appropriate amount of solid electrolyte can improve grain boundary ion transmission and thus improve battery performance.
[0183] The difference between Comparative Example 5 and Example 1 is that conventional alumina ceramic material is coated on the surface of the polymer diaphragm, and the thermodynamic properties of the diaphragm and the electrical properties of the assembled battery are lower than those of all the examples, indicating that the prepared solid electrolyte / high entropy alloy aerogel composite material has an improvement effect on all properties. In Comparative Example 6, a small amount of composite material is added to the diaphragm slurry, and the mechanical and thermal properties of the composite diaphragm are slightly reduced, and the electrical properties of the battery are also reduced to a small extent, indicating that adding an appropriate amount of composite material can comprehensively improve the various properties of the composite diaphragm and the battery.
[0184] Figure 1 This is a SEM image of the cross section of the composite membrane prepared in Example 1, which has a rich pore structure with a porosity of 43.2%, providing a basis for the air permeability of the composite membrane.
[0185] In summary, the present invention comprehensively utilizes the excellent properties of high entropy alloy aerogel and solid electrolyte, adopts the sol-gel method to prepare the solid electrolyte / high entropy alloy aerogel coating, and after coating it on both sides of the diaphragm, obtains a composite diaphragm with excellent comprehensive performance after drying at normal pressure. Compared with similar diaphragm coating materials, the multifunctional diaphragm coating structure prepared by the present invention is more uniform and stable, and after coating on the surface of the lithium battery diaphragm, it has a significant improvement on the high temperature performance and electrical performance of the battery.
[0186] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0187] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.
[0188] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0189] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0190] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite diaphragm, characterized in that: It comprises a base film, and a coating layer arranged on at least one side surface of the base film in the thickness direction; The coating comprises a composite material comprising a high entropy alloy aerogel and a solid electrolyte.
2. The composite diaphragm according to claim 1, characterized in that: The high entropy alloy aerogel includes at least five metal elements of sodium, potassium, calcium, lead, cerium, magnesium, aluminum, zinc, strontium, barium, copper or cobalt; And / or, the solid electrolyte includes at least one of a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte or a polymer solid electrolyte.
3. The composite diaphragm according to claim 1 or 2, characterized in that: The coating also includes a binder; Preferably, the binder includes at least one of polyvinylidene fluoride, polyacrylate, polyimide, polyperfluoroalkoxy, polytetrafluoroethylene, polyacrylonitrile or polyvinyl alcohol.
4. The composite diaphragm according to claim 3, characterized in that: In the composite material, the mass ratio of the high entropy alloy aerogel to the solid electrolyte is (70-90): (10-16); Preferably, the mass ratio of the high entropy alloy aerogel, the solid electrolyte and the binder is (70-90): (10-16): (8-11).
5. The composite diaphragm according to claim 1 or 2, characterized in that: The base film comprises at least one of a polyester film, a polyethylene film or a polypropylene film; And / or, the base film has a thickness of 7 to 9 μm and a porosity of 30% to 40%; And / or, the coating has a thickness of 3 to 5 μm.
6. A method for preparing a composite diaphragm, characterized in that: The method comprises: Dissolving the metal salt in a solvent and adding a thickener to obtain a sol solution; The sol solution is mixed with a solid electrolyte, and the pH value of the system is adjusted to alkaline to obtain a composite gel; Post-processing the composite gel to obtain a composite material comprising a high entropy alloy aerogel and a solid electrolyte; coating a slurry containing the composite material on at least one surface of a base film to obtain a composite diaphragm; The post-treatment process method includes at least one of a heat treatment process, a freeze-thaw cycle process, a chemical vapor deposition process, a physical vapor deposition process or an electrodeposition process.
7. The method for preparing a composite diaphragm according to claim 6, characterized in that: The step of obtaining the sol solution satisfies at least one of the following characteristics (1) to (5): (1) The metal salt comprises a mixture of at least five metal salts; Preferably, the metal salt comprises a mixture of at least five of sodium salt, potassium salt, calcium salt, lead salt, cerium salt, magnesium salt, aluminum salt, zinc salt, strontium salt, barium salt, copper salt or cobalt salt; Preferably, the anion in the metal salt includes at least one of nitrate ion, acetate ion or sulfate ion; (2) The solvent includes alcohol and water; Preferably, the volume ratio of the alcohol to water is 1:(3-4); Preferably, the alcohol includes one or two of methanol, ethanol, propanol, isopropanol, and propylene glycol; (3) The thickener comprises one of polyethylene glycol, polybutylene glycol, polyvinyl alcohol or polyamide alcohol; (4) Based on the mass of the solvent, the mass of the metal salt accounts for 35% to 45% of the mass of the solvent; (5) Based on the mass of the solvent, the mass of the thickener accounts for 1.5% to 2% of the mass of the solvent.
8. The method for preparing a composite diaphragm according to claim 6, characterized in that: The step of obtaining the composite gel satisfies at least one of the following characteristics (1) to (4): (1) The solid electrolyte comprises at least one of a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte or a polymer solid electrolyte; (2) Based on the mass of the solvent, the mass of the solid electrolyte accounts for 5% to 8% of the mass of the solvent; (3) The base used to adjust the pH value of the system includes one or more of aluminum hydroxide, copper hydroxide, zinc hydroxide, ammonia water, and sodium carbonate; (4) The pH value of the regulating system is in the range of 9 to 11.
9. The method for preparing a composite diaphragm according to any one of claims 6 to 8, characterized in that: The heat treatment process is carried out in an inert gas atmosphere, the heating rate of the heat treatment is 5-8°C / min, the heat preservation temperature of the heat treatment is 800-1000°C, and the heat preservation time of the heat treatment is 3h-5h; And / or, after obtaining the composite gel and before the post-treatment, a drying step is also included; and / or, the slurry comprising the composite material comprises the composite material, a binder and water; Preferably, in the slurry, the mass ratio of the composite material, the binder and water is (30-40):(3-6):
100.
10. A battery comprising a separator, characterized in that: The diaphragm is the composite diaphragm according to any one of claims 1 to 5 or the composite diaphragm prepared by the preparation method according to any one of claims 6 to 9.
Citation Information
Patent Citations
Lithium-based high-entropy alloy coating, preparation method and metal lithium battery
CN115976500A
High-entropy alloy aerogel catalyst as well as preparation method and application thereof
CN118422249A
Composite diaphragm, preparation method thereof and battery
CN118943656A
Lithium secondary battery and preparation method therefor
WO2024153058A1
Cited By
Aerogel reinforced composite electrolyte film for solid-state lithium battery and preparation method of aerogel reinforced composite electrolyte film
CN120784431A
Self-repairing polymer solid electrolyte as well as preparation method and application thereof
CN122025839A